2012
DOI: 10.1371/journal.pone.0043866
|View full text |Cite
|
Sign up to set email alerts
|

Functional Biogeography of Ocean Microbes Revealed through Non-Negative Matrix Factorization

Abstract: The direct “metagenomic” sequencing of genomic material from complex assemblages of bacteria, archaea, viruses and microeukaryotes has yielded new insights into the structure of microbial communities. For example, analysis of metagenomic data has revealed the existence of previously unknown microbial taxa whose spatial distributions are limited by environmental conditions, ecological competition, and dispersal mechanisms. However, differences in genotypes that might lead biologists to designate two microbes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Overall, the study demonstrated that environmental temperature influenced the distribution of phylotypes, and hence the diversification and global radiation of the SAR11 clade. These findings corroborate other reports that identify temperature as a factor that controls phylotypes and the global distribution of marine microorganisms 29,32,35,[42][43][44][45][46] , including a study using single-cell genomics 47 .…”
Section: Meromicticsupporting
confidence: 91%
“…Overall, the study demonstrated that environmental temperature influenced the distribution of phylotypes, and hence the diversification and global radiation of the SAR11 clade. These findings corroborate other reports that identify temperature as a factor that controls phylotypes and the global distribution of marine microorganisms 29,32,35,[42][43][44][45][46] , including a study using single-cell genomics 47 .…”
Section: Meromicticsupporting
confidence: 91%
“…The relationships between microbial community composition, diversity and functional potential have been explored in several aquatic bacterial community studies (Langenheder et al, 2005;Szabo et al, 2007;Comte and del Giorgio, 2010;Peter et al, 2011). However, such studies are rarely undertaken in natural systems (but see Parnell et al, 2010;Jiang et al, 2012) and are often conducted as analyses of 'island-like' systems such as batch culture microcosms (Langenheder et al, 2005) where species richness is frequently lowered artificially (Peter et al, 2011;Ylla et al, 2013) or in poorly connected environments where the exchange of microbial taxa among microcosms is otherwise impeded. Thus, it remains unclear the extent to which microbial communities exhibit biogeography in taxonomic or functional attributes across small spatial scales within contiguous landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…Parameter selection procedures proposed in most applications of NMF to biological data are based upon stability of the weight matrix W over several initializations of the iterative algorithm used to solve the problem [12, 13, 15, 16], in particular regarding the clustering of samples. Since our use of NMF focuses on extracting reproducible biological mechanisms characterized by the trait matrix H , we are more interested in biological stability than numerical one.…”
Section: Resultsmentioning
confidence: 99%
“…Since our use of NMF focuses on extracting reproducible biological mechanisms characterized by the trait matrix H , we are more interested in biological stability than numerical one. Therefore, we propose an adaptation of the concordance index developed by [16], which measures the concordance between two matrices of profiles, to evaluate the concordance of the CAFTs computed on independent data sets. In our approach, the reproducibility of H on a new data set is mimicked by repeatedly splitting the set of biological samples, performing the NMF decomposition on each subset and evaluating the similarity between the two trait matrices via the concordance index.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation